2016
DOI: 10.5665/sleep.5826
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training Improves Sleep and Mitigates Cardiovascular Dysfunction in Obstructive Sleep Apnea

Abstract: The results are consistent with our previously published findings in normotensive adults but further indicate that IMT can modulate blood pressure and plasma catecholamines in subjects with ongoing nighttime apnea and hypoxemia. Accordingly, we suggest IMT offers a low cost, nonpharmacologic means of improving sleep and blood pressure in patients who are intolerant of CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
158
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(162 citation statements)
references
References 39 publications
3
158
0
1
Order By: Relevance
“…Recently, we reported that healthy (normotensive) adults and adults with sleep apnoea who perform inspiratory muscle training (IMT) each day for 6 weeks exhibit declines in systolic (SBP) and diastolic blood pressure (DBP; Vranish, & Bailey, , ). Apart from the ability to lower systolic and diastolic blood pressure over a short time course (4–6 weeks) and the abbreviated format of the daily training (∼5 min day −1 ), there are several other features of IMT that set it apart from more traditional aerobic exercise (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that healthy (normotensive) adults and adults with sleep apnoea who perform inspiratory muscle training (IMT) each day for 6 weeks exhibit declines in systolic (SBP) and diastolic blood pressure (DBP; Vranish, & Bailey, , ). Apart from the ability to lower systolic and diastolic blood pressure over a short time course (4–6 weeks) and the abbreviated format of the daily training (∼5 min day −1 ), there are several other features of IMT that set it apart from more traditional aerobic exercise (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements in vascular compliance, therefore, could contribute to slowing down the decrease of vascular elasticity as a normal process during aging, as well as to reducing cardiovascular risk [3]. Although the mechanism for RMT to modify vascular plasticity remains to be determined, supporting evidence comes from the findings that RMT reduces systolic and diastolic blood pressure in both normotensive and hypertensive adults [4,5]. Furthermore, RMT restores impaired peripheral blood flow to resting and exercising limbs in chronic heart failure patients.…”
Section: Effect Of Rmt On Vascular Functionmentioning
confidence: 99%
“…The IMT consists on performing inspirations against a resistance through many mechanisms, it is an easily applied and low-cost intervention, which is also considered clinically significant in the rehabilitation scenario 11 . Studies with different populations point out the improvement of inspiratory muscle force after performing the IMT [9][10][11][12][13][14][15] . In addition, functional capacity and blood pressure also seem to be favored by this training modality 9,13 .…”
Section: Introductionmentioning
confidence: 99%